Evaluating Neighbourhood Accessibility: A Spatial Analysis of Walking Preferences - Shakila Khalid, Nurul; Nasrudin, Na’asah; Osman, Naimah (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine how spatial layout affects parent decision-making of mode choice for school. The spatial layout of the neighbourhood has been analyzed within the scope of integration, connectivity, and street network by using Space Syntax’s axial analysis model. To analyse the spatial quantitative, two parameters in Space Syntax were used: global (Rn) and local integration (R3) to measure the network configuration of street design in the neighbourhood within an 800-meter radius from schools in two different neighbourhoods. The purpose of comparing two (2) different neighbourhood densities and layout patterns—grid and curvilinear—is to hypothesise which built environment characteristics have a strong association with mode choice. The result indicates that the very grid with mainly linear, shortest paths and block lengths that are accessible within children’s walking range is significantly correlated with their choice of school. It is proposed in this paper that streets with a high degree of integration and a school that is adjacent to main streets with the co-presence of attractors such as shophouses, offices, restaurants, open spaces, and other service providers encourage schoolchildren to walk to and from school. This research improves our understanding of the spatial layout of residential buildings and exerts a powerfully influenced children’s active mobility, and a syntax-based study helps to design better-connected street networks in the neighbourhood.